SYNTHESIS AND CHARACTERIZATION OF CoTi(1-X)Mn(X)O3 AS A RADAR ABSORBING MATERIAL - Maspin Apit; Romie Oktovianus Bura; Wisnu Ari Adi; Raden Andhika Ajiesastra (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
To avoid detection from Radio Detection and Ranging (Radar), one of the efforts is to use Radar absorbing material. One of the Radar wave absorbing materials is Perovskite CoTiO3. This Paper investigated the ability of CoTi(1-x)Mn(x)O3 to absorb the Radar wave. CoTi(1-x)Mn(x)O3 with variations x = 0, 0.01, 0.02, and 0.03 have been successfully synthesized using the mechanical milling method. The XRD pattern shows that the sample formed was single phase CoTiO3. Surface morphology resulting from measurements with SEM shows homogeneous particles and an average size of 200 nm. The results of measurements with VNA at X-band frequency (8.20 GHz - 12.4 GHz) show that the absorption ability of electromagnetic waves from CoTiO3 increases with the increase in doping from Mn4+. Maximum results obtained at the composition x=0.03 (CoTi0.97Mn0.03O3) with a reflection loss (RL) value is -14.56 dB (%Abs is 81.3%) at a frequency of 9.96 GHz. This result proves that CoTi(1-x)Mn(x)O3 can be used as a Radar absorbing material at X-band frequency.